Regulatory reporting of non-financial information ‐ examples from the Irish third sector. (1st July 2019) - Clerkin, Brendan; Quinn, Martin
Abstract : Charities are now engaging with the most recent version of the Charities Statement of Recommended Practice (SORP) ‐ the FRS 102 SORP ‐ from the Financial Reporting Council. In this paper we examine a sample of four charities to explore how the non-financial information required by the SORP is communicated. Our findings reveal that the level of information varies, and would seem not to be driven by the charities' size.